Stabilized Phase Variants of Vibrio cholerae El Tor P-18895 - O. V. Markina; A. I. Shelokhovich; A. N. Terent’Ev; O. A. Tatarenko; S. O. Vodop’Yanov; A. B. Mazrukho; L. D. Makedonova; D. I. Kaminsky; I. S. Shestialtynova (Проблемы особо опасных инфекций, 2015)
Produced have been stabilized phase variants of V. cholerae El Tor P-18895 (O- and rugose colonies). Frequency of reversion to initial ST-phenotype does not exceed 10 %. Identity of the origin is verified in VNTR. Evaluated has also been their activity by means of the following diagnostic tests: agglutination assay, sensitivity to diagnostic bacteriophages test, and studies of growth behavior in solid nutrient media. Stabilized variants of V. cholerae El Tor P-18895 can be deployed for further investigations of peculiarities of biofilm formation on various surfaces, bacterial resistance to environmental factors, and for the enhancement of methods for isolation of cholera vibrio variants from ambient environment.